Preparation, Characterization, in-vitro and in-vivo Pharmacokinetic Evaluation of Thermostable Dimethyl Fumarate Cocrystals - Alam Q.; Ganeshpurkar A.; Singh S.K.; Krishnamurthy S. (My University, 2025)
Dimethyl fumarate (DMF) is an FDA-approved drug for treating relapsing-remitting multiple sclerosis; but it is susceptible to sublimation leading to its loss during processing. Cocrystals can protect against thermal energy via the interaction of DMF with a coformer via weak forces of interaction. With this hypothesis, we have, for the first time, prepared DMF cocrystals using the solvent evaporation method using coformers like citric acid and succinic acid screened by in-silico predictions and hydrogen bonding properties. Analysis using infra-red (IR), powder x-ray diffraction (PXRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and sublimation evaluation characterized cocrystals and their thermostability. Comparative analysis of the release profile has been done by dissolution and pharmacokinetic study of DMF and its cocrystals. The cocrystals have improved thermal stability and better pharmacological activities than DMF. In the safety and efficacy evaluation of the formulated cocrystals, they were found to be non-cytotoxic, antioxidant, and inhibiting IL-6 and TNF-α in PBMC induced by lipopolysaccharide (LPS). We have obtained cocrystals of DMF with improved thermal stability and better pharmacological activities than DMF. © 2023 American Pharmacists Association